2003
DOI: 10.1034/j.1600-0404.2003.01357.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical prognosis in hindbrain related syringomyelia

Abstract: The results give evidence for the prognostic importance of creating an adequate artificial cisterna magna. Dorsal-tenting of the duraplasty is an advantageous means against scarring and adhesions, whereby intradural applications such as extensive bipolar coagulation of the cerebellar tonsils should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
0
21
1
1
Order By: Relevance
“…A previous study of surgical prognosis in hindbrain-related syringomyelia, based on 31 patients, found that no patients who received bipolar tonsillar cautery experienced clinical improvement and, in fact, showed a trend toward deteriorated outcome with tonsillar cautery. 2 Our finding of improved outcome with tonsillar cautery was not concordant with this previous study. However, we did conduct our study on a larger sample of patients with syrinx (n = 171), controlling for other variables known to affect outcome.…”
Section: Tonsillar Cautery Independently Predicts Syrinx Improvementcontrasting
confidence: 57%
“…A previous study of surgical prognosis in hindbrain-related syringomyelia, based on 31 patients, found that no patients who received bipolar tonsillar cautery experienced clinical improvement and, in fact, showed a trend toward deteriorated outcome with tonsillar cautery. 2 Our finding of improved outcome with tonsillar cautery was not concordant with this previous study. However, we did conduct our study on a larger sample of patients with syrinx (n = 171), controlling for other variables known to affect outcome.…”
Section: Tonsillar Cautery Independently Predicts Syrinx Improvementcontrasting
confidence: 57%
“…These include the size of the suboccipital craniectomy, a decompression with or without an opening of the dura mater, an opening of the dura with or without closing or patching with dural graft, tonsillectomy, and so on. 1,2,12,19,21,22,24 Overall, surgery has proven to be quite effective. 6,18,24 The most frequently reported complications following CM surgery include pseudomeningocele, 16,25 meningitis, 4 CSF leakage, 25 and cerebellar ptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][65][66][67]70,71,100,[102][103][104][105][106][107][108][109][110][111][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][132]…”
Section: General Informationunclassified
“…4,8,13,14,[16][17][18][19]21,22,29,36,45,48,49,57,62,71,79,82,84,85,95,105,113,[118][119][120][122][123][124][125]127,128,137,149,151 In the pediatric series that reported an association of syringomyelia, of a total of 1678 patients, 673 (40%) harbored a syrinx. [1][2][3]15,24,28,[30][31][32][33]35,41,42,50,51,…”
Section: Incidence Of Syringomyeliamentioning
confidence: 99%